Perceptions of Trade Union Members and the Social Action Perspective - Poole, Michael (Relations industrielles / Industrial Relations, 1981)
This paper aims at presenting the results of a study of trade union members in the United Kingdom and at establishing a central theoretical framework which will facilitate a systematic accumulation of knowledge on this subject.